Cilvēkresursu piesaiste interešu izglītības iestādē - Rage-Raģis, Jānis (Latvijas Universitāte, 2020)
Maģistra darba nosaukums ir „Cilvēkresursu piesaiste interešu izglītības iestādē”. Darba mērķis ir noskaidrot, kāda ir cilvēkresursu piesaistes situācija Rīgas interešu izglītības centros. Maģistra darba teorētiskajā daļā tiek apskatīta interešu izglītības centru vēsture, izglītības un praktisko iemaņu prasības interešu izglītības skolotājam, interešu izglītības centru struktūra un perspektīvas, to finansēšana. Interešu izglītības salīdzinājums Eiropas savienībā, cilvēkresursu menedžments un atalgojums, darba tirgus raksturojums Latvijā, cilvēkresursu vadība, skolotāja darba novērtēšana. Maģistra darba praktiskajā daļā tiek veikts pētījums, lai noskaidrotu interešu izglītības iestāžu vadītāju, skolotāju, vecāku un ekspertu viedokļus par jautājumiem, kas saistīti ar cilvēkresursu piesaisti interešu izglītības centram. Atslēgvārdi: interešu izglītība, neformālā izglītība, interešu izglītības skolotājs, pulciņi, cilvēkresursi.

The title of the Master’s Thesis is „The Attraction of Human Resources in Interest - related Education Institutions”. The aim of the thesis is to identify the current situation of the attraction of human resources in interest – related education institutions in Riga. The theoretical part of the thesis consists of the history of interest – related education centers, the requirements of practical skills for teachers of interest – related education centers, the structure of interest – related education centers and prospects of their financing. Also the comparison of interest - related education in the European Union, characteristics of human resources, management, remuneration, labor market in Latvia, the management of human resources and the evaluation of teacher’s work. The practical part of the thesis consists of research that is carried out to find out the opinions of the managers, teachers, parents and experts of interest - related education institutions on the issues related to the attraction of human resources to the interest – related education centers. Key Words: Interest-related education, non-formal education, non-formal education teacher, activities of non-formal education, human resources.
Attraction of human resources in interest-related education
Keywords: Izglītības vadība; interešu izglītība; neformālā izglītība; interešu izglītības skolotājs; pulciņi; cilvēkresursi